Integração de preços no mercado brasileiro de milho sob a presença de custos de transação no período de 2009 a 2016 - Silva, Maykon Daniel Gonçalves (2017)
The objective of this study is to analyze the integration of prices in the Brazilian maize market, considering the transaction costs. The daily maize prices were analyzed from January 2009 to December 2016, in the physical markets of Sorriso - Mato Grosso, Dourados - Mato Grosso do Sul, Paranaguá and Cascavel - Paraná, Rio Verde - Goiás, Passo Fundo - Rio Grande do Sul and Campinas - São Paulo. The methodology consisted of the unit root test, Granger causality, Johansen cointegration, estimation of the linear error correction vector model (VEC) and Threshold (TVEC) with two regimes . The results indicate that Campinas has a bias and a long-term equilibrium relation with the other markets and the estimation of the TVEC model confirms the presence of a threshold. In the Down regimes, where most of the sample percentage is found, the price changes in Campinas affected the prices of Dourados and Triangulo Mineiro only in the short term, i.e., past price variations. In the Up regimes the price changes in Campinas affected in the short and long term the other physical markets. In addition, the threshold parameters indicate the existence of transaction costs in the interrelationships between prices. So that a price shock resulting from excess demand in Campinas, for example, exceeds 1,22%; 1,45%; 1,26%; 0,9%; 1,27%; 1,03% and 1,39% promote a price adjustment in Cascavel, Dourados, Paranaguá, Passo Fundo, Rio Verde, Sorriso and Triângulo Mineiro, respectively.